Nanopore sequencing of PCR products enables multicopy gene family reconstruction - Alice Namias; Kristoffer Sahlin; Patrick Makoundou; Iago Bonnici; Mathieu Sicard; Khalid Belkhir; Mylène Weill (Computational and Structural Biotechnology Journal, 2023)
The importance of gene amplifications in evolution is more and more recognized. Yet, tools to study multi-copy gene families are still scarce, and many such families are overlooked using common sequencing methods. Haplotype reconstruction is even harder for polymorphic multi-copy gene families. Here, we show that all variants (or haplotypes) of a multi-copy gene family present in a single genome, can be obtained using Oxford Nanopore Technologies sequencing of PCR products, followed by steps of mapping, SNP calling and haplotyping. As a proof of concept, we acquired the sequences of highly similar variants of the cidA and cidB genes present in the genome of the Wolbachia wPip, a bacterium infecting Culex pipiens mosquitoes. Our method relies on a wide database of cid genes, previously acquired by cloning and Sanger sequencing. We addressed problems commonly faced when using mapping approaches for multi-copy gene families with highly similar variants. In addition, we confirmed that PCR amplification causes frequent chimeras which have to be carefully considered when working on families of recombinant genes. We tested the robustness of the method using a combination of bioinformatics (read simulations) and molecular biology approaches (sequence acquisitions through cloning and Sanger sequencing, specific PCRs and digital droplet PCR). When different haplotypes present within a single genome cannot be reconstructed from short reads sequencing, this pipeline confers a high throughput acquisition, gives reliable results as well as insights of the relative copy numbers of the different variants.